Pengembangan E-book Berbasis Canva pada Mata Pelajaran PAI untuk Meningkatkan Hasil Belajar Siswa SMP Kosgoro Jombang - Agustin, Putri; Aisa, Aufia; Rahmawati, Rina Dian (YASIN, 2025)
The low levels of student interest and achievement in Islamic Religious Education (PAI) at SMP Kosgoro Ngusikan Jombang form the basis of this study, largely attributed to the use of conventional and less engaging learning media. This research aims to develop and evaluate the effectiveness of a Canva-based interactive e-book in improving learning outcomes and fostering student interest. The method employed is Research and Development (R&D), using the Borg and Gall model simplified into seven steps according to Sugiyono: identifying potential and problems, data collection, product design, design validation, revision, limited trial, and final revision. The research subjects were ninth-grade students at SMP Kosgoro Ngusikan Jombang in the 2024/2025 academic year. Validation results from media and content experts indicate that the interactive e-book is "highly feasible" in terms of visual design, effectiveness, and interactivity. Product trials demonstrated a significant improvement in student learning outcomes, as shown by the difference in average scores before and after using the media. The study concludes that the Canva-based interactive e-book is effective for PAI instruction. In addition to enhancing academic performance, it provides a more engaging, interactive, and enjoyable learning experience for students.